2017
DOI: 10.1073/pnas.1704847114
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a vesicular ATP release inhibitor for the treatment of neuropathic and inflammatory pain

Abstract: Despite the high incidence of neuropathic and inflammatory pain worldwide, effective drugs with few side effects are currently unavailable for the treatment of chronic pain. Recently, researchers have proposed that inhibitors of purinergic chemical transmission, which plays a key role in the pathological pain response, may allow for targeted treatment of pathological neuropathic and inflammatory pain. However, such therapeutic analgesic agents have yet to be developed. In the present study, we demonstrated tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
90
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(95 citation statements)
references
References 47 publications
2
90
0
Order By: Relevance
“…A previous study indicated that clodronate inhibits vesicular ATP release, and decreases the release of inflammatory mediators, thereby attenuating chronic inflammation (24). In the present study, we found that clodronate also inhibits vesicular ATP release from neutrophils, and reduces neutrophil migration, indicating a novel mechanism through which VNUT mediates its anti-inflammatory effects (Fig.…”
Section: Expression Of Vnut In Human Neutrophilssupporting
confidence: 71%
See 2 more Smart Citations
“…A previous study indicated that clodronate inhibits vesicular ATP release, and decreases the release of inflammatory mediators, thereby attenuating chronic inflammation (24). In the present study, we found that clodronate also inhibits vesicular ATP release from neutrophils, and reduces neutrophil migration, indicating a novel mechanism through which VNUT mediates its anti-inflammatory effects (Fig.…”
Section: Expression Of Vnut In Human Neutrophilssupporting
confidence: 71%
“…3A). This suggests that Recently, we identified a potent allosteric inhibitor of VNUT, clodronate (24).…”
Section: Expression Of Vnut In Human Neutrophilsmentioning
confidence: 99%
See 1 more Smart Citation
“…The former possibility is supported by accumulating evidence for a role of P2X7R in nociception [Jorge et al, 2012; Ochoa-Cortes-et al, 2014]. Furthermore, a vesicular ATP release inhibitor is an effective treatment of neuropathic and inflammatory pain in mice (Kato et al, 2017), presumably by acting at P2X7R or other P2XR.…”
Section: Crohn’s Disease (Cd)mentioning
confidence: 97%
“…111) In addition, a chemical screening of a library identified the antidepressant duloxetine as a clinically approved drug that has an inhibitory effect on rodent and human P2X4R and a reversal effect on the PNI-induced mechanical allodynia. 112) For drugs controlling ATP release, the first-generation bisphosphonate clodronate was identified as a potent and selective allosteric inhibitor for VNUT. Clodronate impaired vesicular ATP release from neurons and attenuated neuropathic pain.…”
Section: Development Of Microglia-targeting Drugsmentioning
confidence: 99%